The diversity of the Quranic discourse in the hypocrites - Zorab Ibrahim Mawlood lak (Zanco Journal of Human Sciences, 2020)
The purpose of this research is to reveal the types of Qur'anic discourse that God has addressed to the hypocrites, the research attempted to extrapolate the types of Qur'anic discourse addressed by God the hypocrites and studied them, the research followed the methodology of the Inductive Method,To follow the different types of discourse in the verses of the Holy Quran, and wrote the interpretations and eloquence, And the analytical approach to analyze and study this diverse discourse, And the deductive approach to identify meanings in the diversity of discourse to the hypocrites in the light of the Holy Quran and books of interpretations, finally the research led to a number of valuable results. Which was the most important, That the most speech addressed to God by the hypocrites was the method of intimidation and seduction, Moreover That diversity of discourse of this category, because people are different nature